2010
DOI: 10.1093/molehr/gaq094
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive expression analysis of prostanoid enzymes and receptors in the human endometrium across the menstrual cycle

Abstract: Prostanoids are well-described primary mediators of inflammatory processes and are essential for the normal physiological function of the female reproductive system. The aim of this study was to determine the temporal expression of the prostanoid biosynthetic enzymes (PTGS1, PTGS2, PTGES, PTGES2, PTGES3, AKR1B1, AKR1C3, CBR1, HPGDS, PTGDS, PTGIS, TBXAS1 and HPGD) and the prostanoid receptors (PTGER1, PTGER2, PTGER3, PTGER4, PTGFR, PTGDR, GPR44, PTGIR and TBXA2R) in the human endometrium throughout the menstrua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 60 publications
10
41
0
Order By: Relevance
“…PGs are catabolized mainly by hydroxyprostaglandin dehydrogenase (HPGD) to terminate their action [17]. Expression of HPGD in the uterine endometrium has been reported for humans [18], mice [19], and cows [20] but not pigs. Expression of PTGS1, PTGS2, PTGES, and CBR1 has been reported in the uterine endometrium during early pregnancy in pigs [9,[21][22][23], but expression of these during the later stage of pregnancy and other enzymes involved in PGE 2 and PGF 2a synthesis and metabolism during pregnancy has not been completely studied in pigs.…”
Section: Introductionmentioning
confidence: 99%
“…PGs are catabolized mainly by hydroxyprostaglandin dehydrogenase (HPGD) to terminate their action [17]. Expression of HPGD in the uterine endometrium has been reported for humans [18], mice [19], and cows [20] but not pigs. Expression of PTGS1, PTGS2, PTGES, and CBR1 has been reported in the uterine endometrium during early pregnancy in pigs [9,[21][22][23], but expression of these during the later stage of pregnancy and other enzymes involved in PGE 2 and PGF 2a synthesis and metabolism during pregnancy has not been completely studied in pigs.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of AKR1C3 in the endometrium was described by Catalano and coworkers who reported peak mRNA expression in endometrial tissue homogenates from the early-secretory phase at a time when early stages of post-ovulatory remodelling and initiation of decidualisation are occurring in the endometrium (Catalano et al 2011). The same study reported that AKR1C3 was immunolocalised to glandular and luminal epithelial cells throughout the menstrual cycle (Catalano et al 2011).…”
Section: Androgen Biosynthesis and Expression Of Steroidmetabolising mentioning
confidence: 74%
“…Weak in the proliferative phase and moderate in the secretory phase protein expression in the endometrial stroma have been contradictory, with expression limited to glandular and luminal epithelium as reported by Catalano and coworkers (Catalano et al 2011); however, Hevir and coworkers demonstrated immunopositive staining in both stromal and epithelial cells (Hevir et al 2011). Our own studies showed conclusively that AKR1C3 mRNA and protein are both detectable in isolated human ESCs, and decidualisation results in a marked increase in AKR1C3 expression consistent with peak expression reported in the early-secretory-phase endometrial tissue homogenates (Gibson et al 2016).…”
Section: Protein Detected In Isolated Escsmentioning
confidence: 94%
“…Also, in female reproduction, PGD 2 is secreted from endometrium and myometrium in greater amounts [21]. Prostaglandin endoperoxidase synthase 1 or 2 (PTGS1 and PTGS2) converts arachidonic acid to PGH 2 which is converted by prostaglandin D synthases HPGDS and PTGDS to PGD 2 [22]. As a cytosolic enzyme, HPGDS is involved in immune response as it is expressed by inflammatory cells including mast cells, antigen-presenting cells, and Th2 cells in mammals.…”
Section: Discussionmentioning
confidence: 99%